Thermally stable transparent polymer films for flexible electronics: Properties and applications - Limin Sun; Dong Zhang; Stephen Z.D. Cheng; Frank W. Harris (Giant, 2023)
This article describes the properties of the thermostable transparent polymer films (TSTPFs), their potential use in display and electronic applications, as well as the potential market size. The property targets for different types of applications including free standing and supported films then are discussed. The development focus in TSTPFs, especially colorless polyimides (CPIs) for organic light emitting diodes (OLEDs), is emphasized. Some thermally stable transparent polymers that have been developed by our company are discussed.